Prescribing high-quality peritoneal dialysis: The role of preserving residual kidney function. Issue 3 (May 2020) - Chen, Chang Huei; Perl, Jeff; Teitelbaum, Isaac
Maintenance of residual kidney function (RKF) is independently associated with increased survival in patients with end-stage renal disease. Presence of RKF is also associated with improved volume status, better nutritional status, reduced erythropoietin requirement, and decreased rate of peritonitis in patients on peritoneal dialysis (PD). Thus, the preservation of RKF is an important therapeutic end point in the management of patients on PD. Measurement of RKF in PD patients should be based on the mean of 24-h urinary creatinine and urea clearances, and ideally, this should be done quarterly. Compared to those started on hemodialysis, patients initiated on PD appear to have slower decline in RKF. The choice of PD modality should be based on patient preference, as there is no clear evidence to date showing one modality is superior than the other in preserving RKF. Peritoneal dialysates with neutral pH and low glucose degradation products seem to have a favorable effect on RKF. An angiotensin-converting enzyme inhibitor or angiotensin receptor blocker should be used whenever possible to preserve RKF and reduce cardiac mortality. Both loop diuretics and icodextrin can be utilized to maintain fluid balance in PD patients. However, caution should be taken to avoid volume depletion which could accelerate RKF decline. Short-term use of aminoglycosides does not have a detrimental impact on RKF, but prolonged use (>3 weeks) should be avoided to minimize the risk of ototoxicity. Lastly, potential nephrotoxic agents such as intravenous contrast should be used judiciously.